Hanging Deaths in Samsun - Aydın, Berna; Turla, Ahmet; Boz, Halil; Karaarslan, Bekir (The Bulletin of Legal Medicine, 2006)
Hanging oneself is a frequently resorted method to commit suicide. Cases of accident and murder are rarely reported. In this descriptive study, we aim to specify the demographic features of those who were killed as a result of hanging and compare the data with the similar studies. For this purpose; records of 61 hanging cases out of 3261 cases of Samsun administration of courthouse archive which a postmortem examination or autopsy was performed in between 1997-2004 were studied retrospectively. Thirtyseven of the cases (60.7%) were male, 24 cases (39.3%) were female. The mean age was 32,38 + 14,15 (11-79) years. The origin was suicide in all the cases. Hanging took place in the house and its adjacent parts in 77.1% cases. There were scene investigation reports and sketch in 91.8% of the cases, however photographs of the scene or victims were available in 55.7% cases. Of cases 77.1% were complete hanging and 82% cases were typical hanging. The ligature mark was observed in all cases and rope was used in 32 cases (52.5%) as ligature. Thirtyeight ecchymoses of soft neck structure and 32 fracture of hyoid hone and/or thyroid cartilage was detected in autopsy performed 51 cases. Seperation was observed in the cervical vertebrae in one case. As is the case in all forensic deaths, the scene investigation should be made, sketches should be drawn, findings should he supported by the photographs to avoid delaying judicial procedures and to acquire accurate results. A proper autopsy should be performed by an expert team to clarify the possible question marks in the course of the judicial procedure. Key words: hanging, suicide, autopsy